2020
DOI: 10.1038/s41598-020-58383-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of stereotactic radiofrequency ablation for very large (≥8 cm) primary and metastatic liver tumors

Abstract: To assess the safety and clinical outcomes of multi-probe stereotactic radiofrequency ablation (SRFA) for very large (≥8 cm) primary and metastatic liver tumors with curative treatment intent. A retrospective, single center study carried out between 01.2005 and 06.2018. 34 consecutive patients had a total of 41 primary and metastatic liver tumors with a median size of 9.0 cm (8.0-18.0 cm) at initial SRFA. Patients were treated under CT guidance using a 3D navigation system. Endpoints consisted of (i) technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Due to the increasing expertise in specialized centres, treatment indications for stereotactic thermal ablation are increasingly expanded. The present summary shows the encouraging results in all reported outcomes including for patients with tumours in di cult intrahepatic locations (centrally, liver dome (39), segment 1(37)), very large tumours (33) and "vanishing" or CT invisible tumours using image fusion (72). In practice, minimally invasive stereotactic ablation approaches are bene cial especially in these situations, where they allow a curative intended treatment when conventional image guidance techniques preclude an e cient and safe targeting.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Due to the increasing expertise in specialized centres, treatment indications for stereotactic thermal ablation are increasingly expanded. The present summary shows the encouraging results in all reported outcomes including for patients with tumours in di cult intrahepatic locations (centrally, liver dome (39), segment 1(37)), very large tumours (33) and "vanishing" or CT invisible tumours using image fusion (72). In practice, minimally invasive stereotactic ablation approaches are bene cial especially in these situations, where they allow a curative intended treatment when conventional image guidance techniques preclude an e cient and safe targeting.…”
Section: Discussionmentioning
confidence: 57%
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitations of RFA are tissue charring, causing an increase in impedance and peripheral tissue cooling, caused by the dissipation of heat by both large blood vessels as well as capillary level micro-perfusion [ 30 ]. Although effective against small (<2 cm) HCCs, achieving adequate margins for larger tumours requires multiple electrodes [ 22 , 31 ]. Due to this limitation, RFA suffers from a relatively high rate of LTP ranging from 10.0 to 39.1% at five years [ 16 , 22 ].…”
Section: Ablative Modalitiesmentioning
confidence: 99%
“…Furthermore, RFA mandates a high level of operator experience in the use of conventional ultrasound- and CT-navigation in order to achieve precise 3D alignment of probes and subsequently create adequately overlapping ablation areas. In that setting, stereotactic RFA as an emerging alternative approach allows for optimal 3D ablation planning and achievement of optimal configuration of the RFA probes, thus creating multiple overlapping coagulation volumes, especially in larger tumors (>5 cm) [ 86 ].…”
Section: Non-surgical Liver-targeted Treatmentsmentioning
confidence: 99%